Lithofacies Interpretation Of Sediment Rocks In The Cipamingkis River Outcrop, Jonggol Area, Bogor District, West Java - Suwondo Suwondo; Mill Sartika Indah; Afzalurrahman Assalam; Muhammad Nafian; Andika Perbawa (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2023)
This research aims to study sedimentary structures and determine the depositional environment of the outcrop in the Cipamingkis River, Jonggol area, Bogor Regency, West Java. The method in this study includes literature studies, field surveys, data interpretation, and facies analysis. The result shows the outcrop in the Cimangkis River can be divided into four (4) sedimentation sequences unit: Claystone Unit (Sequence 1), Limestone/Calsirudit Unit (Sequence 2), Limestone/calcarenite-Calcilutite Unit (Sequence 3), Mudstone/ Calsilutite Unit (Sequence 4). Based on the depositional environment analysis, this outcrop displays characteristics of a shallow marine environment. The Interpretation of facies from outcrops can be used as a reservoir analog and can support subsurface interpretation in the Northwest Java Basin